Paisajes de dependencia en Cochabamba durante el Tawantinsuyu y la colonia temprana - Gabelmann, Olga (2024)
One of the major transformations of the landscape and ecosystem that the Cochabamba Valley underwent was due to the conquest by the Incas, which caused the displacement of its population and the relocation of mitimaes from all parts of Tawantinsuyu to work the newly expropriated state lands. Thus, the valley became a new centre of dependency and consolidation of the Inca state. Only shortly afterwards, the Spanish conquest, through new displacements of labour, created colonial dependencies, but based on already-existing structures, especially on the state farms. The lands themselves became the nucleus of colonial exploitation and therefore the focus of conflicts between Spaniards and indigenous people, but also between the indigenous people themselves. Our aim is to understand the intertwining of the dependencies created in the course of both conquests, which were reflected in various modifications of the landscape and ecosystem. To do so, we innovatively use combined archaeological (GIS mapping, survey, excavation) and ethnohistorical (data systematisation and toponymy) methods, so as to understand the location and use of land in the changing dependency landscapes of the Cochabamba valley from the Late Intermediate Period (1000/1100-1470 AD) to the early colonial period (1538-1700 AD).